KEPEMIMPINAN KEPALA SEKOLAH PADA RINTISAN SEKOLAH BERTARAF INTERNASIONAL (Studi situs di SMP Negeri 1 Ungaran) - SUKOCO , BAGUS (2011)
There are two goals want to be reached in this research: 1) to know the characteristic of leadership of Principal of School at RSBI SMP Negeri 1 Ungaran. 2) to know the strategy that be used by the Principal in controlling the quality of school of RSBI SMP Negeri 1 Ungaran.